Internationalisation of the Islamic thought: the contributions of Sayyed Ismail (1936-2010) / Sayyed Mohamed Muhsin and Mohd. Noh Abdul Jalil - Muhsin, Sayyed Mohamed; Abdul Jalil, Mohd. Noh (Academy of Contemporary Islamic Studies (ACIS), 2021)
This paper examines the intellectual contributions of Sayyed Ismail Bukhari (1936-2010), a great scholar, author and reformer from South India. Sayyed Ismail, who is also locally known as Panoor Thangal, produced seminal works on Quranic exegesis, hadith, fiqh and theology during his lifetime. Despite the profound personality and pivotal works, no serious studies are found which critically scrutinise his theses on Islamic thought and religious studies. In addition, his books, mainly written in Arabic and some of them even published in some Arab countries, shed light on his Islamic thought, which upholds the dimensions of relevantization of Islamic knowledge. He exclusively chose Arabic, not his mother tongue Malayalam, in his writings for a reason. His target audience is not limited to his community in Kerala only but also the Muslim world. This paper analyses his works to further understand the contributions and impacts of Sayyed Ismail to Islamic thought in light of his various academic engagements and activism. Sayyed Ismail is indeed a reformer from Kerala whose reform works involve bringing the Muslim communities to champion the cause of humanity based on the teachings of Islam.